Filming the Glial Dreams: Real-Time Imaging of Cannabinoid Receptor Trafficking in Astrocytes - Alexei Verkhratsky (ASN Neuro, 2009)
How does the brain process incoming information and produce thoughts? These questions represent, to all likelihood, the most challenging matters ever faced by natural sciences, matters which may never be fully comprehended. The evolution of the nervous system that, in about billion of years, brought into existence the human brain progressed through an ever-increasing complexity of neural networks. This evolution began from the diffuse nervous system, in which primordial neurons were able to sense the environmental inputs and convey them to effector organs and to the neighbouring neurons. At the next evolutionary stage the conglomerates of neuronal cell bodies, the ganglia, appeared, thus forming the primitive centralized nervous system. The developments which ensued went through a continuous increase in complexity of neuronal conglomerates, which eventually formed the central nervous system, which attained maximal perfection in mammals. In this issue of ASN NEURO , Osborne et al. have described details of real-time imaging of cannabinoid receptor trafficking in astrocytes, a technique that will help to elucidate the role of these receptors in the ever-increasing complex neural networks.